Multi-product exporters: Costs, prices and markups on foreign vs domestic markets - Catherine Fuss (National Bank of Belgium, 2020)
After establishing that exporters obtain higher margins than non-exporters, the paper takes a new look at export premia by comparing multi-product exporters' costs, prices and markups on the domestic and foreign markets. This firm-product-market analysis is made possible thanks to a unique dataset for Belgian manufacturing firms over 1996-2016. Firm-product estimates of marginal costs are obtained following De Loecker et al. (2016) methodology, based on firm-product production data. Combined with firm-product international transaction data, firm-product unit values can be computed separately for the domestic market and foreign markets. Markups can then be recovered at the firmproduct- market level from observed unit values and estimated marginal costs. The empirical results suggest that firms select their best products, the ones with lower marginal cost, for foreign markets. They partly translate this cost advantage into lower prices, but essentially extract higher margins from these.
Keywords: D22; D24; F14; 330; markups; multi-product firms; pricing decisions; international trade